APPLICATION OF A-PRF IN AN AREA WITH NON-INTEGRATED XENOGRAFT - Antoaneta Mlachkova; Zdravka Pashova-Tasseva; Hristina Maynalovska; Krassimira Gogova; Ivan Ivanov (Journal of IMAB, 2023)
Background: Xenografts are well-studied materials that are often used in regenerative dentistry. Nowadays the number of surgeries involving bovine‑derived xenografts in implant dentistry has increased significantly. However, the long-term success of these materials is still not well studied. A-PRF has been used as an autogenous product that can increase the predictability of the clinical procedure by introducing many platelets growth factors. Purpose: to describe a difficult for diagnostic and treatment clinical case and to propose a clinical protocol for resolving similar complications that can occur after guided bone regeneration. Materials and methods: 41 years old woman complains of pain, edema and inability to chew on the upper right quadrant after a history of placed dental implants and GBR procedure. A full thickness flap was reflected starting from tooth #11 to #16. A thorough decontamination of the affected area has been done with Piezoelectric instruments and A-PRF has been introduced to improve healing process. The flap was repositioned to its original position and sutured with single interrupted resorbable 6/0 sutures. Two weeks after the procedure of surgical removal of the xenograft the patient is relieved from all preoperative symptoms and complaints. Results: The normal architecture of the residual bone and alveolar mucosa is restored. A new CBCT is taken to evaluate the new clinical situation. Conclusion: The case demonstrates that the use of bone substitutes and especially xenografts should be done with caution because they are not resorbable and a potential infection around the graft particles may have long-term biological complications.